Desenvolvimento de modelos de ponto crítico para quantificação de danos causados pelo complexo de doenças foliares em soja - Martins, Fernando Geraldo (2007)
Among the factors that contribute for the reduction of soybean [Glycine max (L.) Merril] crop yield are the diseases. Among them powdery mildew, the end seasons disease and more recently the asian rust have contributed for the reduction of the yield potential. The main goal of this work was to obtain the relationship between crop grain yield and foliar intensity of the diseases. The work was carried out at the Cotrijal s Technology and Harvest Diffusion Center in Não-Me-Toque, in the 2003/04, 2004/05 and 2005/06 growing seasons. The reduction caused to soybean grain yield, attributed to the complex of leaf diseases, supply information to optimize the use of chemicals in the control of these diseases. As a specific objective, threshold equations of the functions of damages have been generated to accomplish the calculation of economic damage threshold (LDE). The equations of the functions of damage with greater R2 allowed to estimate the LDE at different phenologic stages of the crop, serving as an approach to indicate the time for chemical control. The maximum damage caused by the disease complex reached 21% for powdery mildew, 40% for the end season diseases and, 28% for the rust